2008
DOI: 10.1179/174313408x361199
|View full text |Cite
|
Sign up to set email alerts
|

Work-related Musculoskeletal Disorders in Sonography and the Alexander Technique

Abstract: Work-related musculoskeletal disorder (WRMSD) is a problem affecting growing numbers of sonographers. The condition often leads to considerable pain for the individuals concerned and inconvenience for departments struggling to cope with increasing workloads. Employers and equipment manufacturers are making efforts to address the problem, but the number of cases of WRMSD continues to increase. This study looks at a different approach to tackling the problem, introducing student sonographers to a technique often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 5 publications
(5 reference statements)
0
15
0
Order By: Relevance
“…The programme consisted of educational lectures ⁄ group discussions with nurses, physiotherapists and psychologists, auto-hypnosis and relaxation, personal exercise training and AT sessions. Finally, in the occupational setting, a study of group AT instruction for medical sonographers (N = 96) delivered with the aim of reducing work-related musculoskeletal disorders revealed that 86% found that AT was relevant to the practice of ultrasound and 83% thought that they would be able to apply what they had learnt to their work (37,38).…”
Section: Participants' Perceptionsmentioning
confidence: 99%
“…The programme consisted of educational lectures ⁄ group discussions with nurses, physiotherapists and psychologists, auto-hypnosis and relaxation, personal exercise training and AT sessions. Finally, in the occupational setting, a study of group AT instruction for medical sonographers (N = 96) delivered with the aim of reducing work-related musculoskeletal disorders revealed that 86% found that AT was relevant to the practice of ultrasound and 83% thought that they would be able to apply what they had learnt to their work (37,38).…”
Section: Participants' Perceptionsmentioning
confidence: 99%
“…This was also highlighted by Gibbs and Young. 20 One factor that respondents suggested aggravated symptoms of WRMSD in a study of 2963 ultrasound practitioners, was transducer pressure. 1 Ideally, the transducer should be held using a light grip with minimal or no pressure applied.…”
Section: Transducer Grip and Pressurementioning
confidence: 99%
“…14,37 The use of the Alexander technique has also been investigated for sonographers, to help improve body awareness and posture. 8,20 Dynamic exercises can be used to warm up muscles, prior to beginning a scanning list, in the same way that a warm up is used prior to any form of exercise. Research evidence suggests possible benefits from stretching between patients.…”
Section: Physical Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, only 9(22%) had prescribed medication but no official report was made to the management of the respective institutions, others were on self-medication. Treatment for WRMSD often has a poor outcome because the affected person goes back to the same environment that initially produced the injury [15].…”
Section: Discussionmentioning
confidence: 99%